Soil Bacterial Community Responses to N Application and Warming in a Qinghai-Tibetan Plateau Alpine Steppe - Mu, Zhiyuan; Dong, Shikui; Li, Yaoming; Li, Shuai; Shen, Hao; Zhang, Jing; Han, Yuhui; Xu, Yudan; Zhao, Zhenzhen (Frontiers in Ecology and Evolution, 2021)
Nitrogen deposition and climate warming may alter soil bacterial communities, but little is known about the response of soil bacteria in alpine steppe to these changes. We designed an field experiment consisting of four treatments, no-N application with no-warming, N application(8 kg N ha−1 year−1 ) with no-warming, warming with no-N application, N application(8 kg N ha−1 year−1 ) with warming, in the northeastern Qinghai-Tibetan Plateau to observe changes in soil bacterial communities of alpine steppe in response to nitrogen application and warming. Our objectives were to investigate (1) what changes in soil bacterial diversity and community structure would occur under simulated nitrogen deposition and warming conditions, and (2) what are the key environmental factors responsible for these changes. The results showed that soil bacterial diversity and community composition did not change significantly in the short term at this level of nitrogen application and warming. The warming treatment had a significant effect on bacterial overall composition, rare species composition and individual bacterial taxa, and the interaction between nitrogen application and warming had a significant effect on community β-diversity. Above-ground plant variables were highly correlated with the bacterial community. Nitrogen application and warming did not significantly alter the distribution range of the bacterial community. The results of this experiment suggest that soil bacterial communities can remain relatively stable at this level of simulated nitrogen application and warming and that short-term climate change may be safe for local soil bacterial communities.